Does the Gut Microbiota Influence Immunity and Inflammation in Multiple Sclerosis Pathophysiology? - Monika Adamczyk-Sowa; Aldona Medrek; Paulina Madej; Wirginia Michlicka; Pawel Dobrakowski (Journal of Immunology Research)
Aim. Evaluation of the impact of gut microflora on the pathophysiology of MS. Results. The etiopathogenesis of MS is not fully known. Gut microbiota may be of a great importance in the pathogenesis of MS, since recent findings suggest that substitutions of certain microbial population in the gut can lead to proinflammatory state, which can lead to MS in humans. In contrast, other commensal bacteria and their antigenic products may protect against inflammation within the central nervous system. The type of intestinal flora is affected by antibiotics, stress, or diet. The effects on MS through the intestinal microflora can also be achieved by antibiotic therapy and Lactobacillus. EAE, as an animal model of MS, indicates a strong influence of the gut microbiota on the immune system and shows that disturbances in gut physiology may contribute to the development of MS. Conclusions. The relationship between the central nervous system, the immune system, and the gut microbiota relates to the influence of microorganisms in the development of MS. A possible interaction between gut microbiota and the immune system can be perceived through regulation by the endocannabinoid system. It may offer an opportunity to understand the interaction comprised in the gut-immune-brain axis.